Building Global Democracy? : Civil Society and Accountable Global Governance / [electronic resource] - Scholte, Jan Aart (Cambridge : Cambridge University Press, 2011)
The scale, effectiveness and legitimacy of global governance lag far behind the world's needs. This path-breaking book examines how far civil society involvement provides an answer to these problems. Does civil society make global governance more democratic? Have citizen action groups raised the accountability of global bodies that deal with challenges such as climate change, financial crises, conflict, disease and inequality? What circumstances have promoted (or blocked) civil society efforts to make global governance institutions more democratically accountable? What could improve these outcomes in the future? The authors base their argument on studies of thirteen global institutions, including the UN, G8, WTO, ICANN and IMF. Specialists from around the world critically assess what has and has not worked in efforts to make global bodies answer to publics as well as states. Combining intellectual depth and political relevance, Building Global Democracy? will appeal to students, researchers, activists and policymakers.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Democratization; Civil society; International organization